Health technology assessment and reimbursement policy for oncology orphan drugs in Central and Eastern Europe - Malinowski, Krzysztof Piotr; Kawalec, Paweł; Trąbka, Wojciech; Sowada, Christoph; Petrova, Guenka; Manova, Manoela; Savova, Alexandra; Draganić, Pero; Slabý, Juraj; Männik, Agnes; Márky, Kristóf; Rugaja, Zinta; et al. (Orphanet journal of rare diseases, 2020)
BACKGROUND: The reimbursement of orphan drugs (OD) is an increasingly important for country policymakers, and still insufficiently understood, especially in Central and Eastern Europe. The aim of this research was to provide a comprehensive description of country-specific health technology assessment (HTA) policies as well as evaluate the percentage of HTA recommendations and reimbursement decisions for oncology OD. In addition, the study was designed to elucidate the impact of reimbursement of these drugs on the public budget and the agreement between HTA recommendations and reimbursement decisions in the analysed countries. A questionnaire survey was used to collect data on the reimbursement status, HTA recommendation, marketing authorisation, and public expenses on reimbursement in 2014, 2015, and 2016 for all oncology drugs with an orphan designation by the European Medicine Agency in 2017 in Bulgaria, Croatia, Czechia, Estonia, Hungary, Latvia, Lithuania, Poland, Romania, and Slovakia. The agreement between the HTA recommendation and reimbursement status was assessed using the kappa coefficient. The Pearson's correlation was used to analyse the relationship between gross domestic product (GDP) and GDP per capita and reimbursement expenses. RESULTS: A total of 36 drugs were analysed (25% conditionally approved; 5.56% approved under exceptional circumstances). The share of reimbursed drugs ranged from 11.11% in Latvia to 41.67% in Poland. The highest share of positive recommendations was observed for Bulgaria and Estonia (36.11%), and the lowest, for Latvia (11.11%). The agreement varied from 0.4 for Poland to 1 for Latvia, Hungary, and Slovakia. Expenses were correlated with GDP (0.95 [0.81-0.99]), and not with GDP per capita (0.54 [- 0.136 to 0.873]). Expenses per capita were not correlated with GDP per capita (0.52 [- 0.15 to 0.87]). CONCLUSIONS: In Hungary, Latvia, and Slovakia, a positive recommendation was associated with a reimbursement, and a negative one, with the lack of reimbursement. The reimbursement of oncology OD is associated with a growing burden for public budget, and the expenses are correlated with the total GDP. The highest share of drugs with any recommendation was observed in Poland, and the lowest, in Latvia and Romania. The share of reimbursed drugs was the lowest in Latvia and the highest in Poland.
Keywords: Latvia; Orphan Drug Production; výroba orphan drugs; postup; lidé; Technology Assessment, Biomedical; Evropa; Poland; Reimbursement; Orphan drugs; léčivé přípravky; Humans; Central and Eastern Europe; Česká republika; zdravotní politika; Health Policy; Oncology; Policy; Czech Republic; Polsko; Europe; Lotyšsko; Health technology assessment; Pharmaceutical Preparations; hodnocení biomedicínských technologií